ORANG YANG SAKIT JIWA KEBERAGAMAANNYA - Ramadan Lubis (NIZHAMIYAH, 2016)
Al-Quran surah al-Baqara verse 10 states "in their hearts is a disease, then God plus disease and for them a painful punishment, because they lie". Although this verse mentions a sick heart, but actually they are sick soul. Qalbun in the Koran can be interpreted An-nafs or soul. The soul is the totality of man physically and psychologically. Religious attitude of the mentally ill is found in those who have had a background of religious life is disrupted. The religious attitude by the consistency between the beliefs of the religion as a cognitive element, feeling for religion as an element of an effective and behavior towards religion as a conative element. Thus, the religious attitude is a complex integration between religious knowledge and religious acts in a person. This shows that religious attitudes regarding or closely associated with psychiatric symptoms. Deviant religious attitude occurs when a person's attitude towards trust and confidence in the religious affiliations of change.